Elastic Fiber Supercapacitors for Wearable Energy Storage. Issue 13 (17th May 2018) - Qin, Si; Seyedin, Shayan; Zhang, Jizhen; Wang, Zhiyu; Yang, Fangli; Liu, Yuqing; Chen, Jun; Razal, Joselito M.
Abstract: The development of wearable devices such as smart watches, intelligent garments, and wearable health‐monitoring devices calls for suitable energy storage devices which have matching mechanical properties and can provide sufficient power for a reasonable duration. Stretchable fiber‐based supercapacitors are emerging as a promising candidates for this purpose because they are lightweight, flexible, have high energy and power density, and the potential for easy integration into traditional textile processes. An important characteristic that is oftentimes ignored is stretchability—fiber supercapacitors should be able to accommodate large elongation during use, endure a range of bending motions, and then revert to its original form without compromising electrical and electrochemical performance. This article summarizes the current research progress on stretchable fiber‐based supercapacitors and discusses the existing challenges on material preparation and fiber‐based device fabrication. This article aims to help researchers in the field to better understand the challenges related to material design and fabrication approaches of fiber‐based supercapacitors, and to provide insights and guidelines toward their wearability. Abstract : Current research progress on stretchable fiber‐based supercapacitors is summarized and the existing challenges in material preparation and fiber‐based device fabrication are discussed. This article aims to help researchers in the field better understand the challenges related to material design and fabrication approaches of fiber‐based supercapacitors, and to provide insights and guidelines toward their wearability.